Pengaruh Metode Waterfall dalam Penyempurnaan Proses Pengembangan Sistem Informasi Akademik secara Sistematis: Impact of Waterfall Method on Systematic Academic Information System Development - Po Abas Sunarya; Untung Rahardja; Santoso, Nuke Puji Lestari; Mulyati; Mustofa, Kenny Ilyas; Bennet, Daniel (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2025)
Academic information systems play a crucial role in supporting the operations of educational institutions, particularly in managing complex data. The main challenge in their development is ensuring that the process is structured, efficient, and aligned with user needs. The Waterfall method, as one of the sequential and systematic development approaches, is often used in information system development projects. However, its effectiveness in the context of academic information systems requires further analysis. This study aims to analyze the impact of the Waterfall method on improving the development process of academic information systems. The research focuses on three main aspects: time efficiency, cost, and the quality of the final output. Both quantitative and qualitative descriptive approaches were employed in this study. Data were collected through in-depth interviews with system developers, surveys of users (academic administration, lecturers, and students), and case studies at educational institutions using the Waterfall method. The results show that the Waterfall method provides a clear structure in the development process of academic information systems. This has a positive impact on time efficiency and the quality of the final output. However, the main drawback of this method is its lack of flexibility in addressing changing needs that often arise during the project. In conclusion, the Waterfall method is effective for academic information system development projects with stable and well-defined requirements. This study recommends exploring a hybrid approach, such as combining Waterfall with Agile, to improve responsiveness to changes in user needs in the future.